2015
DOI: 10.11646/phytotaxa.207.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Impatiens sahyadrica sp. nov (Balsaminaceae)—a new species from southern Western Ghats, India

Abstract: Impatiens sahyadrica (Balsaminaceae), a new scapigerous balsam from Silent Valley National Park, southern Western Ghats is described and illustrated. The new species is phenotypically similar to I. lawsonii. However, it differs from the latter in its smaller flowers; oblong, free upwardly curved basal lobes of the lateral united petals; smaller dorsal auricle and curved spur. A detailed description, notes on distribution, biotic association and relevant taxonomic notes are provided along with colour photograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Extensive field surveys were conducted in Kerala during the period 2019-2021. Analysis of relevant literature (Hooker and Thomson 1860;Hooker 1875Hooker , 1904Hooker -1906Hooker , 1908aHooker , b, 1910Hooker , 1911Dessai and Janarthanam 2011;Bhaskar 2012;Hareesh et al 2015;Ramasubbu et al 2015Ramasubbu et al , 2017Bhaskar and Sringeswara 2017;Mani et al 2018) and careful examination of preserved specimens preserved at various herbariums (TBGT, KFRI, MH, USF, K, CALI, and CMPR) (acronyms according to Thiers (2021) [continuously updated]) were undertaken to complete the study. Furthermore, distribution map was created using QGIS Version 3.14.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive field surveys were conducted in Kerala during the period 2019-2021. Analysis of relevant literature (Hooker and Thomson 1860;Hooker 1875Hooker , 1904Hooker -1906Hooker , 1908aHooker , b, 1910Hooker , 1911Dessai and Janarthanam 2011;Bhaskar 2012;Hareesh et al 2015;Ramasubbu et al 2015Ramasubbu et al , 2017Bhaskar and Sringeswara 2017;Mani et al 2018) and careful examination of preserved specimens preserved at various herbariums (TBGT, KFRI, MH, USF, K, CALI, and CMPR) (acronyms according to Thiers (2021) [continuously updated]) were undertaken to complete the study. Furthermore, distribution map was created using QGIS Version 3.14.…”
Section: Methodsmentioning
confidence: 99%
“…More than 106 species are endemic to the Western Ghats, of which 80% are endangered (Bhaskar 2012). Moreover, several endemic taxa have been recently reported from various parts of the Western Ghats (Hareesh et al 2015;Chhabra et al 2016;Vishnu et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…During floristic explorations over the past decade on the Nilgiri plateau, the authors came across three interesting scapigerous Impatiens . After study with perusal of relevant literature (Arnott , , Hooker , Gamble , Fyson , Barnes , Bhaskar , , Vivekananthan et al , Basha , Dessai and Janarthanam , Bhaskar , Narayanan et al , Hareesh et al , , Prabhukumar et al ), three scapigerous balsams have been found to be new to science. Detailed description, distribution, biotic association, colour photographs and illustrations of these taxa are provided here.…”
Section: Impatiens Kawttyana Chhabra Et Ramneek Sp Nov (Fig )mentioning
confidence: 99%
“…According to recent estimates, more than 106 species of Impatiens are endemic to the Western Ghats, of which more than 80% are endangered (Bhaskar ). Moreover, several possibly endemic new taxa have been recently reported from various parts of the Western Ghats (Hareesh et al , Prabhukumar et al , Chhabra et al ).…”
mentioning
confidence: 99%